Application of catalyst in NORR reaction

By using honeycomb carbon support and Cu metal cluster/single-atom copper catalyst in the NORR reaction, the problems of slow reaction kinetics and hydrogen evolution interference were solved, and the effect of efficient conversion of low concentrations of nitric oxide to ammonia was achieved, which significantly improved the catalyst Faraday efficiency and selectivity.

CN119121283APending Publication Date: 2024-12-13CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411058482.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has slow reaction kinetics in the NORR reaction catalyzing the conversion of nitric oxide to ammonia, especially in the case of low concentrations of nitric oxide, which is difficult to achieve efficient conversion.

Method used

Using honeycomb carbon as a support, loading Cu metal clusters and single-atom copper, the catalyst is prepared by freeze-drying and hydrogen calcining steps, inhibiting metal atom migration and agglomeration, enhancing the electronic coupling effect and porous structure of the catalyst, significantly improving the Faraday efficiency of the NORR reaction .

Benefits of technology

It significantly improves the NORR activity and selectivity of the catalyst, inhibits the hydrogen evolution side reaction, improves the conversion rate and Faraday efficiency of low concentrations of nitric oxide, and shows excellent electrocatalytic performance and performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121283A_ABST
    Figure CN119121283A_ABST
Patent Text Reader

Abstract

The invention discloses application of a catalyst in NORR reaction, and belongs to the technical field of environmental protection. According to the application of the catalyst in NORR reaction provided by the invention, the catalyst comprises honeycomb carbon and Cu loaded on the surface of the honeycomb carbon; wherein the existence form of Cu comprises at least one of metal clusters and monatomic copper; the honeycomb carbon is a pyrolysis product of an aldol condensation polymer. According to the application provided by the invention, the Faraday efficiency of the NORR reaction can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental protection, and in particular to application of a catalyst in NORR reaction. Background Art

[0002] Nitric oxide is one of the main flue gas pollutants, mainly from industrial waste gas, automobile exhaust, thermal power generation, etc. Its accumulation in the atmosphere seriously damages the ecological environment (including acid rain, photochemical smog, and ozone depletion) and affects the balance of the nitrogen cycle. Therefore, it is of great significance to convert nitric oxide pollutants into harmless nitrogen or high-value-added nitrogen-containing chemicals. At present, selective catalytic reduction technology is the most common method for removing nitric oxide. Although this technology can convert nitric oxide into nitrogen that is harmless to the environment, it consumes precious ammonia or hydrogen in the process. In contrast, electrocatalytic nitric oxide conversion strategies powered by renewable solar energy, wind energy, etc. are more environmentally friendly and sustainable. This mild catalytic process can convert nitric oxide pollutants into valuable nitrogen-containing chemicals, especially ammonia, which is an indispensable active nitrogen source in modern industry and agriculture. Compared with nitrogen, nitric oxide molecules are easier to activate because of their lower bond binding energy. In addition, the standard reduction potential of the nitric oxide to ammonia reaction (NORR) is more positive than that of the hydrogen evolution reaction (HER), so NORR is thermodynamically easier to achieve than HER. However, in reality, NORR is seriously interfered by the competitive HER due to its slow reaction kinetics, especially at low concentrations of nitric oxide.

[0003] In summary, it is very necessary to design a catalyst that can efficiently activate low-concentration nitric oxide molecules and convert them into ammonia with high selectivity. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes an application of a catalyst in a NORR reaction, which can effectively improve the Faraday efficiency of the NORR reaction.

[0005] According to an embodiment of the first aspect of the present invention, there is provided an application of a catalyst in a NORR reaction, the catalyst comprising honeycomb carbon, and Cu supported on the surface of the honeycomb carbon; wherein the existence form of Cu comprises at least one of a metal cluster and a single atomic copper;

[0006] The honeycomb carbon is a thermal decomposition product of an aldol condensation polymer.

[0007] The application of the embodiments of the present invention has at least the following beneficial effects:

[0008] The honeycomb carbon has a spatial restriction effect, which can inhibit the migration of metal single atoms on the surface of the honeycomb carbon, thereby preventing the metal atoms from agglomerating into a pure metal phase; the porous structure of the honeycomb carbon can significantly improve the enrichment of low-concentration nitric oxide molecules on the catalyst surface; the metal copper clusters and / or copper single-atom catalysts loaded on the surface of the honeycomb carbon have a strong electronic coupling effect, which can promote electron transfer at the catalytic interface, accelerate the activation of nitric oxide molecules, and enhance the NORR activity of the catalyst; the catalyst has excellent performance in the electrocatalytic nitric oxide reduction reaction. Specifically, the catalyst provided by the present invention can effectively inhibit the hydrogen evolution reaction at a high potential, and the nitric oxide conversion rate and Faraday efficiency are significantly higher than those of commercial platinum / carbon and pure copper catalysts; it also has the advantages of stable performance and recyclability. On the whole, in the application provided by the present invention, the catalyst can improve the reaction kinetics of NORR, significantly inhibit the HER side reaction, and has the ability to highly selectively convert low-concentration nitric oxide into ammonia.

[0009] According to some embodiments of the present invention, the pores in the honeycomb carbon have a pore diameter of 5 to 700 nm.

[0010] According to some embodiments of the present invention, the honeycomb carbon is doped with N.

[0011] According to some embodiments of the present invention, in the catalyst, when Cu exists in the form of single-atom copper, it is coordinated with N. This can improve the structure and performance stability of the single-atom copper. More specifically, the copper in the single-atom copper is coordinated with 3 N atoms.

[0012] According to some embodiments of the present invention, the specific surface area of ​​the catalyst is 80 to 280 m 2 / g. Specifically, it can be 100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g or about 279.2m 2 / g.

[0013] According to some embodiments of the present invention, the carbon content in the catalyst is 96-99 wt %, for example, 97-98 wt %.

[0014] According to some embodiments of the present invention, the content of Cu in the catalyst is 0.1-1 wt %, for example, 0.25-0.5 wt %, or more specifically, about 0.3% or about 0.4%.

[0015] According to some embodiments of the present invention, the content of N in the catalyst is 1 to 3 wt %, for example, 1.4 to 2.3 wt %, or more specifically, about 1.8% or about 2%.

[0016] According to some embodiments of the present invention, the catalyst is a black solid.

[0017] According to some embodiments of the present invention, the catalyst is prepared by a preparation method comprising the following steps:

[0018] S1. mixing the copper salt, the nitrogen-containing ligand and the honeycomb carbon in water and freeze-drying the mixture;

[0019] S2. calcining the product obtained in step S1 in an atmosphere containing hydrogen.

[0020] The mechanism of the preparation method is as follows:

[0021] In step S1, the copper ions in the copper salt are coordinated with the nitrogen-containing ligands, which fully improves the dispersibility of copper and avoids agglomeration on the surface of the honeycomb carbon in the later stage.

[0022] In step S1, the function also includes uniform adsorption, that is, the copper-nitrogen-containing ligand complex is fully and uniformly adsorbed on the honeycomb carbon surface. In the process, the honeycomb carbon provides sufficient nanospace for adsorbing and storing the complex formed by copper and nitrogen-containing ligand.

[0023] In step S1, freeze drying is used to remove the solvent, which can retain the internal structure of the material and the integrity of its activity without destroying the sample structure; traditional drying methods such as baking will cause the material to shrink and destroy its structure, so freeze drying can better maintain the porous structure inside the catalyst and confine the copper metal therein; on the contrary, the catalyst will suffer from accumulation of copper precursors due to structural collapse during ordinary drying, resulting in a large number of particles agglomerating and being unable to form single atoms.

[0024] In step S2, the main function is to reduce copper and reduce copper ions to copper element; at the same time, under the action of hydrogen, the anions of the copper salt combine with hydrogen and are discharged from the system. According to the adjustment of the amount of copper and the distribution state in step S1, the state of Cu obtained in step S2 is a cluster (slightly aggregated) and / or a single atom (basically no aggregation). The secondary function of step S2 is to dope part of the N in the nitrogen-containing ligand introduced in the previous step into the honeycomb carbon to further improve the conductivity of the honeycomb carbon.

[0025] Furthermore, since the catalyst of the present invention is used for NORR reaction, other nitrogen-containing gases cannot be used for calcination to avoid significant impact on subsequent applications; the present invention uses hydrogen as a reducing gas, which not only has a good reducing effect, but also does not consume honeycomb carbon as a reducing agent (if consumed, it will affect the structure of the honeycomb carbon), and does not leave any residual by-products, which provides a basis for the application of the obtained catalyst in NORR reaction.

[0026] According to some embodiments of the present invention, in step S1, the copper salt includes at least one of CuSO4, CuCl2 and CuC2O4.

[0027] According to some embodiments of the present invention, in step S1, the nitrogen-containing ligand includes at least one of 1,10-phenanthroline, glycine (CAS: 56-40-6) and ethylenediamine (CAS: 107-15-3).

[0028] According to some embodiments of the present invention, in step S1, the mass ratio of the copper salt to the nitrogen-containing ligand is 0.085:0 to 0.4. For example, it can be about 0.085:0.1, 0.085:0.2 or about 0.085:0.3. In actual production, the role of the nitrogen-containing ligand is to improve the Faradaic efficiency of the NORR reaction in the application.

[0029] According to some embodiments of the present invention, in step S1, the molar volume ratio of the copper salt to the water used is 2 to 25 mmol / L. For example, it can be about 2.5 mmol / L, 3 mmol / L, 4 mmol / L, 5 mmol / L, 6 mmol / L, 8 mmol / L, 10 mmol / L, 15 mmol / L, 20 mmol / L or about 22 mmol / L.

[0030] According to some embodiments of the present invention, in step S1, the method for preparing honeycomb carbon comprises the following steps:

[0031] S1a. The monomers are subjected to aldol condensation under the action of a base catalyst to obtain a polymer; the monomers include at least one of an aldehyde and a ketone.

[0032] S1b. Carbonizing the polymer.

[0033] According to some embodiments of the present invention, in step S1a, the monomer includes at least one of acetaldehyde and acetone.

[0034] According to some embodiments of the present invention, in step S1a, the monomer further comprises ethanol. Specifically, the hydroxyl group in the ethanol can react with the carbonyl group in the acetaldehyde or acetone.

[0035] According to some embodiments of the present invention, in step S1a, the base catalyst includes at least one of KOH and NaOH.

[0036] According to some embodiments of the present invention, in step S1a, the mass volume ratio of the base catalyst to the monomer is 1 g: 3-7 mL, for example, about 1 g: 4 mL, 1 g: 5 mL or about 1 g: 6 mL.

[0037] According to some embodiments of the present invention, in step S1a, the aldol condensation comprises stirring and standing in sequence. The stirring time is 50 to 120 minutes; for example, it can be about 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes or about 110 minutes. The standing time is 5 to 10 days; for example, it can be about 7 days or 8 days.

[0038] According to some embodiments of the present invention, in step S1a, the apparent color of the polymer is yellow.

[0039] According to some embodiments of the present invention, in step S1b, the carbonization temperature is 300-600°C, and specifically may be about 400°C or about 500°C.

[0040] According to some embodiments of the present invention, in step S1b, the carbonization time is 60 to 120 minutes, for example, about 80 minutes, 90 minutes, 100 minutes, 11 minutes or about 120 minutes.

[0041] According to some embodiments of the present invention, in step S1b, the carbonization temperature rise rate is 5-20°C / min, for example, 8°C / min, 10°C / min or about 15°C / min.

[0042] According to some embodiments of the present invention, in step S1b, the carbonization atmosphere is selected from argon.

[0043] According to some embodiments of the present invention, step S1b further comprises washing and drying the obtained carbonized product after the carbonization.

[0044] The washing includes concentrated salt acid washing and stirring water washing in sequence. The duration of the concentrated salt acid washing is not limited, as long as the washing liquid stops bubbling; the water washing duration is 24 to 72 hours, and more specifically can be about 30 hours, 40 hours, 48 ​​hours, 50 hours, 60 hours or about 70 hours. Therefore, the concentrated salt acid washing can wash away the alkaline catalyst and the reaction products of the alkaline catalyst and air. In this process, the alkaline catalyst also serves as a pore-forming agent, that is, the concentrated salt acid washing process also serves as a pore-forming agent, which can further enrich the pore structure of the obtained honeycomb carbon and enhance the catalytic performance of the catalyst.

[0045] According to some embodiments of the present invention, the drying temperature is 60-85° C., for example, specifically about 80° C.

[0046] According to some embodiments of the present invention, in step S1, the mass volume ratio of the honeycomb carbon and other components is 50-200 mg: 0.01-10 mL. For example, it can be 150 mg: 0.01-10 mL. More specifically, it can be 150 mg: 8-10 mL.

[0047] According to some embodiments of the present invention, in step S1, the mixing time is 20 to 60 minutes, for example, about 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes or about 50 minutes.

[0048] According to some embodiments of the present invention, in step S1, the mixing method includes at least one of stirring and ultrasound.

[0049] According to some embodiments of the present invention, step S1 further includes performing preliminary freezing before freeze drying. The preliminary freezing includes freezing in a refrigerator for 2 to 5 hours, for example, about 3 hours or about 4 hours.

[0050] According to some embodiments of the present invention, in step S1, the freeze-drying temperature is -48 to -56°C, for example, about -50°C or about -55°C.

[0051] According to some embodiments of the present invention, in step S1, the freeze-drying time is 18 to 48 hours, and specifically may be about 20 hours, 24 hours, 30 hours or about 40 hours.

[0052] According to some embodiments of the present invention, the specific steps of step S1 are:

[0053] providing a mixed solution comprising a copper salt and a nitrogen-containing ligand;

[0054] The mixed solution and the honeycomb carbon are mixed in water and then the solvent is removed.

[0055] Although the order of adding the copper salt, the nitrogen-containing ligand and the honeycomb carbon does not affect the type and properties of the product, the above-mentioned addition steps can more conveniently control the dosage and concentration of the copper salt / nitrogen-containing ligand.

[0056] According to some embodiments of the present invention, the appearance of the mixed solution is a blue to light blue solution.

[0057] According to some embodiments of the present invention, the method for preparing the mixed solution comprises mixing a copper salt, a nitrogen-containing ligand and water, wherein the mixing time is 25 to 35 minutes, for example, specifically about 30 minutes.

[0058] According to some embodiments of the present invention, in step S2, the calcination temperature is 300-700°C, and specifically may be about 400°C, 500°C or about 600°C.

[0059] According to some embodiments of the present invention, in step S2, the calcination time is 60 to 120 minutes, for example, about 80 minutes, 90 minutes or about 100 minutes.

[0060] According to some embodiments of the present invention, in step S2, the heating rate of the calcination is 5-15°C / min, for example, about 10°C / min.

[0061] According to some embodiments of the present invention, in step S2, the volume percentage of hydrogen in the atmosphere used for the calcination is 3-10%, for example, about 5% or about 6%.

[0062] According to some embodiments of the present invention, in step S2, the atmosphere used for the calcination further includes argon. More specifically, the atmosphere used for the calcination is a mixture of hydrogen and argon.

[0063] According to some embodiments of the present invention, the NORR reaction is an electrochemical catalytic reaction, and the raw materials for preparing the cathode used in the electrochemical catalytic reaction include the catalyst;

[0064] During the electrochemical catalytic reaction, the gas to be treated containing NO is introduced into the electrolyte used.

[0065] The mechanism of the NORR reaction is as follows: the catalyst on the cathode first adsorbs NO, and then under the action of electrolysis and the catalyst, nitric oxide is converted into ammonia. The details are as follows:

[0066] NO+5e - +5H + →H2O+NH3.

[0067] According to some embodiments of the present invention, the cathode includes a cathode carrier and a catalyst loaded on the surface of the cathode carrier.

[0068] The cathode carrier includes at least one of conductive carbon paper, conductive glass, carbon felt and carbon cloth.

[0069] The single-sided apparent area of ​​the cathode carrier is 0.5 to 2 cm 2 For example, it can be about 1 cm 2 , or about 1.5cm 2 .

[0070] Furthermore, the area of ​​the catalyst loaded on one side of the cathode carrier is 0.5 to 1 cm 2For example, it can be about 1 cm 2 .

[0071] According to some embodiments of the present invention, the method for preparing the cathode comprises coating a slurry containing the catalyst on the surface of the cathode carrier and then drying the slurry.

[0072] The raw materials for preparing the slurry also include ethanol, water and 5wt% Nafion solution. The volume ratio of ethanol to water is 1:1; for example, it can be 495μL:495μL. The volume ratio of ethanol to 5wt% Nafion solution is 495:5-20μL; for example, it can be about 495:10.

[0073] The solid-liquid ratio in the slurry is 2-10 mg:1 mL, for example, 5 mg:1 mL or about 8 mg:1 mL.

[0074] The volume of slurry required to be coated on one side of a single cathode carrier is 10-100 μL, for example, about 20 μL, 30 μL, 40 μL, 50 μL, 60 μL, 70 μL, 80 μL or about 90 μL.

[0075] The preparation method of the slurry includes ultrasonically mixing the raw materials for preparing the slurry. Specifically, the ultrasonic mixing time is 45 to 60 minutes. For example, it can be about 50 minutes or about 55 minutes.

[0076] There is no requirement for the drying temperature and duration, and the slurry only needs to be dried.

[0077] According to some embodiments of the present invention, the anode used in the electrochemical catalytic reaction is a platinum electrode.

[0078] According to some embodiments of the present invention, the electrolyte is a saline solution, wherein the solute of the saline solution includes at least one of potassium sulfate, sodium sulfate and phosphate buffer.

[0079] According to some embodiments of the present invention, the concentration of the electrolyte is 0.01-1 mol / L, for example, about 0.1 mol / L, 0.5 mol / L or about 0.8 mol / L.

[0080] According to some embodiments of the present invention, the pH of the electrolyte is 5.5 to 7.5, for example, about 5.8, 6.0, 6.5 or about 7.0.

[0081] According to some embodiments of the present invention, the volume concentration of NO in the gas to be treated is 5 to 20%. For example, it can be about 10% or about 15%. At low concentrations, due to the slow reaction kinetics of NORR, its Faraday efficiency and output efficiency are both low. In the application provided by the present invention, due to the use of a specific catalyst and specific NORR reaction conditions, it has a high efficiency even for low concentrations of NO.

[0082] According to some embodiments of the present invention, the gas to be processed further includes a carrier gas, and the carrier gas includes argon.

[0083] According to some embodiments of the present invention, the flow rate of NO is 30-100 sccm, for example, about 40 sccm, 50 sccm, 60 sccm or about 80 sccm.

[0084] According to some embodiments of the present invention, the temperature of the NORR reaction is 15-35° C., for example, specifically about 25° C.

[0085] According to some embodiments of the present invention, the Faradaic efficiency of the electrochemical catalytic reaction is 70-90%.

[0086] According to some embodiments of the present invention, the voltage of the electrochemical catalytic reaction is 0 to -1.0 V vs. RHE, for example, about -0.1 V, -0.2 V, -0.3 V, -0.4 V, -0.5 V, -0.6 V, -0.7 V, -0.8 V or -0.9 V.

[0087] According to some embodiments of the present invention, the duration of the electrochemical catalytic reaction is 30 to 60 minutes. For example, it may be about 40 minutes or about 50 minutes.

[0088] According to some embodiments of the present invention, the yield of NH3 generated by the NORR reaction is 40 to 220 mmol / gh, for example, about 41 mmol / gh, 121 mmol / gh, 123 mmol / gh, 158 mmol / gh or 216 mmol / gh.

[0089] According to some embodiments of the present invention, the Faradaic efficiency of the NORR reaction is 70-90%, for example, about 71.1%, 82.2%, 89.3%, 84.8% or 81.9%.

[0090] Unless otherwise specified, "room temperature" in the present invention means 25°C±2°C.

[0091] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0092] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0093] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0094] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0095] Figure 1 This is the SEM test result of the catalyst obtained in Example 1 of the present invention.

[0096] Figure 2 This is the XRD test result of the catalyst obtained in Example 1 of the present invention.

[0097] Figure 3 It is the XAS test result of the catalyst obtained in Example 1 of the present invention, including its XANES spectrum (a) and the corresponding FT-EXAFS and its fitting spectrum.

[0098] Figure 4 These are the TEM test results of the catalysts obtained in Example 1 (a, b) and Comparative Example 5 (c, d) of the present invention.

[0099] Figure 5 These are the UV-Vis test results of the electrolyte obtained in Example 1 of the present invention, blank control A and blank control B.

[0100] Figure 6 These are the linear sweep voltammetry test results of the cathodes obtained in Example 1 of the present invention and Comparative Example 1 in a 0.1M K2SO4 solution saturated with argon.

[0101] Figure 7 It is the yield and Faraday efficiency of ammonia obtained by NORR reaction in Example 5 of the present invention and Comparative Examples 1 to 5.

[0102] Figure 8 It is the yield and Faraday efficiency of ammonia obtained by NORR reaction in Examples 1 to 5 of the present invention and Comparative Examples 6 to 9. DETAILED DESCRIPTION

[0103] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0104] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0105] Unless otherwise specified, the reaction temperature is room temperature.

[0106] Example 1

[0107] This example provides an application of a catalyst in a NORR reaction, wherein:

[0108] The catalyst is prepared by a preparation method comprising the following steps:

[0109] S1. Add 85 mg CuCl2·2H2O and 0.1 g C 12 Pour 200 mL of water into a beaker containing H8N2 (CAS: 66-71-7) and stir for 30 min to obtain a light blue copper metal precursor solution (called mixed solution);

[0110] S1a. After 16 g of NaOH and 80 mL of acetone were mixed and stirred for 1 h, the mixture was placed at room temperature for one week to obtain a yellow carbon polymer;

[0111] S1b. The obtained yellow carbon polymer was heated to 500°C at a heating rate of 10°C / min under an argon atmosphere and calcined for 2h;

[0112] Add concentrated hydrochloric acid dropwise to the beaker containing the calcined product until the solution stops bubbling, and filter to obtain a black powder;

[0113] The black powder was washed with water for 48 h and dried at about 80° C. to obtain honeycomb carbon (PC);

[0114] S1c. 150 mg of honeycomb carbon and 10 mL of the mixed solution were mixed and stirred for 5 min, and the resulting mixture was ultrasonicated for 30 min;

[0115] The obtained mixture is placed in a refrigerator and frozen for 2 to 3 hours (as long as blocks are formed); and freeze-dried for 24 hours (temperature is about -50°C) to achieve the effect of removing the solvent.

[0116] S2. The black powder obtained in step S1 is placed in a 5% hydrogen atmosphere (the balance is argon), heated to 500°C at a heating rate of 10°C / min and calcined for 2h to obtain a catalyst (referred to as Cu-CuN3 / PC).

[0117] The cathode for NORR reaction is prepared using the above catalyst:

[0118] At room temperature, 5 mg of the catalyst obtained in this example, 495 μL of ethanol, 495 μL of water and 10 μL of 5% Nafion solution were mixed and ultrasonicated for 60 min to make a slurry. 20 μL of the slurry was dripped on a 2 cm 2 On carbon paper, the effective drop coating area is 1cm 2 , dried with infrared lamp to obtain cathode.

[0119] To carry out NORR reaction:

[0120] The cathode obtained in this example, the platinum anode, and the Ag-AgCl reference electrode constitute a three-electrode system;

[0121] 0.1 mol / L potassium sulfate aqueous solution was used as the electrolyte (pH = 5.8);

[0122] 10% nitric oxide gas (nitric oxide + argon, the volume percentage of nitric oxide is 10%, and the flow rate is 50 sccm) is continuously introduced into the electrolyte, and a constant potential (E = -0.1 V. vs RHE) electrochemical catalytic reaction is carried out at room temperature for 1 hour.

[0123] Example 2

[0124] This example provides an application of a catalyst in a NORR reaction, which is different from Example 1 in that:

[0125] The constant potential used for the electrochemical catalytic reaction was -0.3 V.

[0126] Example 3

[0127] This example provides an application of a catalyst in a NORR reaction, which is different from Example 1 in that:

[0128] The constant potential used in the electrochemical catalytic reaction was -0.5 V.

[0129] Example 4

[0130] This example provides an application of a catalyst in a NORR reaction, which is different from Example 1 in that:

[0131] The constant potential used for the electrochemical catalytic reaction was -0.7 V.

[0132] Example 5

[0133] This example provides an application of a catalyst in a NORR reaction, which is different from Example 1 in that:

[0134] The constant potential used for the electrochemical catalytic reaction was -0.9V.

[0135] Comparative Example 1

[0136] This example provides an application of a catalyst in a NORR reaction, which is different from Example 5 in that:

[0137] Excluding the process of preparing the catalyst, in other processes, the catalyst of Example 1 was replaced with an equal amount of commercial 20% Pt / C powder.

[0138] Comparative Example 2

[0139] This example provides a NORR reaction, which is different from Example 5 in that:

[0140] It does not include the process of preparing the catalyst or the process of preparing the cathode.

[0141] In the NORR reaction, the cathode of Example 1 was replaced with a metal copper sheet of the same size.

[0142] Comparative Example 3

[0143] This example provides an application of a catalyst in a NORR reaction, which is different from Example 5 in that:

[0144] Excluding the process of preparing the catalyst, in other processes, the catalyst of Example 1 is replaced by an equal amount of the honeycomb carbon prepared in step S1b of Example 1.

[0145] Comparative Example 4

[0146] This example provides an application of a catalyst in a NORR reaction, which is different from Example 5 in that:

[0147] Excluding the process of preparing the catalyst, in other processes, the catalyst of Example 1 was replaced with an equal amount of commercial activated carbon (Japanese Kuraray activated carbon was used, with a measured specific surface area of ​​1587.6 m 2 / g).

[0148] Comparative Example 5

[0149] This example provides an application of a catalyst in a NORR reaction, which is different from Example 1 in that:

[0150] The preparation process of the catalyst does not include steps S1a to S1b, and in other steps, the honeycomb carbon is replaced with an equal amount of commercial activated carbon.

[0151] Comparative Example 6

[0152] This example provides an application of a catalyst in a NORR reaction, which is different from Comparative Example 5 in that:

[0153] The constant potential used for the electrochemical catalytic reaction was -0.3 V.

[0154] Comparative Example 7

[0155] This example provides an application of a catalyst in a NORR reaction, which is different from Comparative Example 5 in that:

[0156] The constant potential used in the electrochemical catalytic reaction was -0.5 V.

[0157] Comparative Example 8

[0158] This example provides an application of a catalyst in a NORR reaction, which is different from Comparative Example 5 in that:

[0159] The constant potential used for the electrochemical catalytic reaction was -0.7 V.

[0160] Comparative Example 9

[0161] This example provides an application of a catalyst in a NORR reaction, which is different from Comparative Example 5 in that:

[0162] The constant potential used for the electrochemical catalytic reaction was -0.9V.

[0163] Test Example 1

[0164] In this example, the structural morphology, crystal phase composition and elemental composition of the catalyst obtained in Example 1 were tested by SEM, XRD, BET and XPS. The SEM results showed that the catalyst after high-temperature hydrogen reduction maintained a honeycomb porous structure with a pore size distribution between 5 and 700 nm. The specific results are as follows: Figure 1 The BET test results further show that the specific surface area of ​​the catalyst obtained in Example 1 is 279.2 m 2 / g. The presence of these rich pore structures can effectively promote the enrichment of low-concentration nitric oxide molecules by the obtained catalyst, thereby inhibiting hydrogen evolution on the catalyst surface and improving the selectivity of the catalyst for converting nitric oxide into ammonia.

[0165] The XRD test results show that the catalyst obtained in Example 1 has a characteristic broad diffraction peak at 26.2°, corresponding to the (002) plane of graphite carbon; another weak diffraction peak at 43.3° can be indexed to the (111) crystal plane of metal Cu (PDF#85-1326). This result confirms the existence of metal Cu clusters in honeycomb carbon. The XRD test results are as follows Figure 2 shown.

[0166] The composition and content of other elements in the catalyst obtained in Example 1 were obtained by XPS testing. The results showed that the catalyst contained about 0.3% copper, 2.3% nitrogen and 97.4% carbon.

[0167] Test Example 2

[0168] In this example, synchrotron XAS and (HR)TEM were used to further test the microstructure of the catalysts obtained in Example 1 and Comparative Example 5. The morphology of the catalyst obtained in Example 1 shows the skeleton structure of the honeycomb carbon; and the extremely fine metal Cu clusters in the honeycomb carbon; while Comparative Example 5 uses commercial activated carbon to replace the honeycomb carbon, in which Cu is more likely to agglomerate to form larger nanoparticles. This also shows that the porous structure of honeycomb carbon can effectively inhibit the migration of Cu atoms on its surface and prevent the aggregation of copper clusters. The specific test results are as follows: Figure 4 As shown; among them, Figure 4 (a) is a TEM image of the catalyst obtained in Example 1, Figure 4 (b) is a HRTEM image of the catalyst obtained in Example 1. Figure 4 (c) is a TEM image of the catalyst obtained in Comparative Example 5, Figure 4 (d) is the HRTEM image of the catalyst obtained in Comparative Example 5.

[0169] Comparing the X-ray absorption near edge structure (XANES) spectra of CuO and Cu standard samples, it was found that the valence state of Cu in the catalyst obtained in Example 1 was between 0 and +2, and front peaks appeared at 8977eV and 8985eV, corresponding to the 1s→3d transition and 1s→4p transition of Cu, respectively. The corresponding Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum showed that There is a peak corresponding to the Cu-Cu bond at about A weak peak caused by the coordination of Cu and N atoms also appears at . This indicates that the obtained catalyst contains not only Cu-Cu bonds, but also Cu-N coordination bonds. Further fitting revealed that the Cu atoms in the obtained catalyst are mainly coordinated with 3 N atoms. The specific test results are as follows Figure 3 As shown. Figure 3 (a) is the XANES spectrum of the catalyst obtained in Example 1, Figure 3(b) is the corresponding FT-EXAFS spectrum.

[0170] Test Example 3

[0171] In this example, the indophenol blue spectrophotometry was used to determine the products of the NORR reaction in the example and the comparative example. The specific test method was as follows: the electrolyte, buffer solution, NaClO solution (0.05 mol / L) and sodium nitroferricyanide solution (1 wt.%) were mixed in a volume ratio of 2:2:1:0.2 and incubated at room temperature for 2 h to obtain a mixed test solution; wherein the electrolyte was the electrolyte after the NORR reaction in the example or the comparative example, the solution after NO electrolysis at an open circuit voltage (the actual current was 0, and no substantial electrolysis was performed) was used as a blank control A (referred to as OCP in the figure), and the electrolyte in which the gas introduced did not include NO but only included argon for NORR reaction was used as a blank control B (referred to as Ar in the figure); the base liquid of the buffer solution was an aqueous solution of 1 mol / L NaOH, to which salicylic acid (final concentration 5 wt.%) and sodium citrate (final concentration 5 wt.%) were then added. The mixed test solution was subjected to ultraviolet-visible (UV-Vis) measurement using absorbance at a wavelength of 655 nm, and the absorbance measurement range was 500-800 nm.

[0172] By comparing the spectral test results of the electrolyte obtained in Example 3, blank control A and blank control B, it is found that only the electrolyte of Example 3 turns green after the NORR reaction and the absorption peak of ammonia appears at 655nm, indicating that the product of the NORR reaction is ammonia, which mainly comes from the electrolytic conversion of NO, and NO is basically not converted under open circuit voltage. The test results of Example 3, blank control A and blank control B are as follows: Figure 5 The test results of other embodiments are similar to those of embodiment 3.

[0173] Test Example 4

[0174] In this example, the hydrogen evolution activity of the cathode used in Example 1 and Comparative Example 1 was tested respectively. In Ar-saturated K2SO4 solution, the cathode mainly undergoes hydrogen evolution reaction. By measuring the linear scanning voltammetry of the obtained cathode (scan rate of 10mV / s, voltage range of 0.1~-1.0V.vs RHE), it was found that the cathode in Example 1 showed significantly weaker hydrogen evolution activity than Comparative Example 1, indicating that compared with the commercial 20% Pt@C catalyst, the catalyst used in the present invention can more effectively inhibit the occurrence of hydrogen evolution reaction in the NORR reaction, thereby promoting the conversion of NO to NH3. The specific test results are as follows Figure 6 shown.

[0175] Test Example 5

[0176] In this example, the ammonia yield and the Faraday efficiency of the NORR reaction in the examples and comparative examples were tested respectively.

[0177] The ammonia production test method is as follows:

[0178] The absorbance of a series of concentrations (c = 0, 0.04, 0.08, 0.12, 0.16 and 0.2 mol / L, the same as in Test Example 3, except that the electrolyte in Test Example 3 was replaced with an equal amount of ammonium sulfate of a specific concentration) of standard ammonia solution was measured by indophenol blue spectrophotometry, and a concentration-absorbance standard curve (A = 2.631c + 0.0498, R 2 =0.999).

[0179] The absorbance of ammonia in the examples and comparative examples was measured by indophenol blue spectrophotometry, and the ammonia concentration was calculated by the above standard linear equation. The ammonia yield was calculated based on the mass of the catalyst loaded in the cathode, the volume of the electrolyte used, and the time taken for the NORR reaction. The specific calculation formula is:

[0180]

[0181] The Faraday efficiency test method is as follows:

[0182] The concentration of ammonia in the electrolytes obtained in the embodiment and the comparative example was measured respectively, and the Faraday efficiency was calculated according to the total charge consumed by the reaction. The specific calculation formula is:

[0183]

[0184] Total charge

[0185] The specific results of the above tests and calculations are as follows: Figure 7 (Example 5, Comparative Examples 1 to 4), Figure 8 (Examples 1 to 5 and Comparative Examples 5 to 9) and as shown in Table 1.

[0186] Table 1 Faradaic efficiency and ammonia of NORR reaction of examples and comparative examples

[0187] Group Abbreviation in the figure (potential V) <![CDATA[Ammonia production mmol h -1 g -1 cat > Faraday efficiency % Example 1 <![CDATA[Cu-CuN3 / PC(-0.1)]]> 78.2 71.1 Example 2 <![CDATA[Cu-CuN3 / PC(-0.3)]]> 121.4 82.2 Example 3 <![CDATA[Cu-CuN3 / PC(-0.5)]]> 123.3 89.3 Example 4 <![CDATA[Cu-CuN3 / PC(-0.7)]]> 157.9 84.8 Example 5 <![CDATA[Cu-CuN3 / PC(-0.9)]]> 215.8 81.9 Comparative Example 1 Pt@C(-0.9) 90.4 7.2 Comparative Example 2 Cu(-0.9) 149.5 35.7 Comparative Example 3 PC(-0.9) 28.2 35.2 Comparative Example 4 AC(-0.9) 25.3 18.2 Comparative Example 5 <![CDATA[Cu-CuN3 / AC(-0.1)]]> 50.2 55.4 Comparative Example 6 <![CDATA[Cu-CuN3 / AC(-0.3)]]> 63.9 57.9 Comparative Example 7 <![CDATA[Cu-CuN3 / AC(-0.5)]]> 55.2 57.1 Comparative Example 8 <![CDATA[Cu-CuN3 / AC(-0.7)]]> 74.8 67.9 Comparative Example 9 <![CDATA[Cu-CuN3 / AC(-0.9)]]> 160.4 31.3

[0188] The results show that as the electrolysis voltage increases, the ammonia production increases, but the trend of the Faraday efficiency (FE) is slightly different. At E = -0.5V, the FE of NO conversion to ammonia is obviously the highest, and the selectivity of NO conversion to ammonia is the highest at this time; as the voltage continues to increase, the system is affected by the hydrogen evolution side reaction, and the FE decreases slightly; but since the increase in voltage leads to an increase in electrical energy, the overall ammonia production increases with the increase in voltage.

[0189] It can be seen from Example 5 and Comparative Examples 1 to 2 that under high electrolysis voltage (E=-0.9V.vs ​​RHE), since the metallic copper clusters and copper single atom catalysts in the obtained catalyst have strong electronic coupling, they can promote electron transfer at the catalytic interface and accelerate the activation of nitric oxide molecules. Therefore, the catalyst obtained in the example exhibits higher NORR activity than commercial platinum / carbon and pure copper catalysts; in addition, since the porous nitrogen-rich honeycomb carbon promotes the enrichment of low-concentration nitric oxide molecules on the surface of the obtained catalyst, the catalyst used in the example can better suppress HER side reactions than commercial platinum / carbon, and exhibits higher ammonia selectivity and higher ammonia yield and Faraday efficiency.

[0190] It can be seen from Comparative Examples 3 to 4 that the porous honeycomb carbon (PC) prepared in the present invention, as a cathode electrode, exhibits higher ammonia yield and Faraday efficiency than commercial activated carbon (AC), which once again shows that as a carbon carrier, PC can more effectively enrich low-concentration nitric oxide molecules due to its rich pore network, thereby inhibiting hydrogen evolution and improving ammonia selectivity.

[0191] Comparison of Examples 1 to 5 and Comparative Examples 5 to 9 shows that the catalyst prepared by the present invention has a higher ammonia yield and Faraday efficiency than commercial activated carbon (AC) when the carbon substrate is honeycomb carbon (PC). This is related to the existence form of Cu in the catalyst obtained by the present invention. In the comparative example, the integrated large particles of copper lead to a reduction in the exposed catalytic sites and a decrease in the NORR catalytic activity.

[0192] Although, within the point value range verified in the examples of the present invention, the catalyst used in the examples has the highest ammonia selectivity at E=-0.5V, it does not exclude that better results may be obtained within other condition ranges provided by the present invention.

[0193] In summary, the application provided by the present invention has a better ammonia yield and Faraday efficiency by utilizing a special catalyst and selecting suitable reaction conditions. At the same time, the HER side reaction can be significantly suppressed during the application process, and it has the ability to highly selectively convert low-concentration nitric oxide into ammonia.

[0194] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. Use of a catalyst in a NORR reaction, characterized in that: The catalyst includes honeycomb carbon and Cu supported on the surface of the honeycomb carbon; wherein the existence form of Cu includes at least one of metal clusters and single-atom copper; The honeycomb carbon is a thermal decomposition product of an aldol condensation polymer.

2. The use according to claim 1, characterized in that: The catalyst is prepared by a preparation method comprising the following steps: S1. mixing the copper salt, the nitrogen-containing ligand and the honeycomb carbon in water and freeze-drying the mixture; S2. calcining the product obtained in step S1 in an atmosphere containing hydrogen.

3. The use according to claim 2, characterized in that: In step S1, the copper salt includes at least one of CuSO4, CuCl2 and CuC2O4; and / or, in step S1, the nitrogen-containing ligand includes at least one of 1,10-phenanthroline, glycine and ethylenediamine.

4. The use according to claim 2 or 3, characterized in that: In step S1, the mass ratio of the copper salt to the nitrogen-containing ligand is 0.085:0-0.4; and / or, in step S1, the molar volume ratio of the copper salt to the water used is 2-25 mmol / L.

5. The use according to claim 2, characterized in that: In step S1, the mass volume ratio of the honeycomb carbon and other components is 50-200 mg: 0.01-10 mL.

6. The use according to claim 2, characterized in that: In step S2, the calcination temperature is 300-700°C; and / or, in step S2, the calcination time is 60-120 minutes.

7. The use according to claim 1, characterized in that: The NORR reaction is an electrochemical catalytic reaction, and the raw materials for preparing the cathode used in the electrochemical catalytic reaction include the catalyst; During the electrochemical catalytic reaction, the gas to be treated containing NO is introduced into the electrolyte used.

8. The use according to claim 7, characterized in that: In the gas to be treated, the volume concentration of NO is 5-20%; and / or the flow rate of NO is 30-100 sccm.

9. The use according to claim 7, characterized in that: The voltage of the electrochemical catalytic reaction is 0 to -1.0 V vs. RHE.

10. The use according to any one of claims 7 to 9, characterized in that: The Faraday efficiency of the NORR reaction is 70-90%; and / or the yield of NH3 generated by the NORR reaction is 40-220 mmol / gh.